Cárie dentária e aumento de volume gengival em pacientes ortodônticos - Pinto, Alice Souza (2017)
This thesis is composed by three articles, whose main objectives were: 1. To determine the association between the duration of fixed orthodontic treatment and the occurrence of gingival enlargement (paper 1) and dental caries activity (paper 2) among orthodontic patients; 2. To evaluate the incidence/increment of active caries lesions in orthodontic patients after a 1-year follow-up (paper 3). The sample consisted of individuals who sought and/or were undergoing orthodontic treatment at an orthodontic graduate program in Santa Maria-RS (Brazil). In the cross-sectional studies (papers 1 and 2), 260 patients were divided into four distinct groups: G0, without the orthodontic device (control group); G1, using fixed apparatus for one year (10-14 months); G2, using fixed apparatus for two years (22-26 months), and G3, using fixed apparatus for three years (34-38 months). In the longitudinal study (paper 3), the sample consisted of 135 patients divided into two distinct groups: G0, without the orthodontic device (control group); G1, individuals using the fixed orthodontic appliance for one year (10-14 months). Initially, the subjects answered a questionnaire on socio-demographic characteristics and oral hygiene habits. Then, individuals were submitted to clinical examination, which included bacterial biofilm accumulation index, gingival index, professional cleaning, drying, dental caries index, and evaluation of gingival enlargement. The association between the outcomes and the independent variables was assessed using Poisson regression models. In papers 1 and 2, respectively, it was found an increasing occurrence of gingival enlargement and caries activity between groups G0, G1 and G2 (p <0.05), with no difference between G2 and G3 groups (P> 0.05). It was also observed (paper 1) that individuals submitted to orthodontic treatment had a 20- 28-fold increased risk of presenting a gingival enlargement than those without orthodontic appliances (G1, rate ratio [RR] = 20.2, 95% CI = 9.0-45.3; G2, RR = 27.0, 95% CI = 12.1-60.3; G3, RR = 28.1, 95% CI = 12.6-62.5). As shown in paper 3, the incidence of active caries lesions was 4.8% in G0 and 39.6% in G1. Patients with a fixed orthodontic appliance for one year presented an approximately 9-fold increased risk of developing at least one active caries lesion when compared to G0 (adjusted incidence rate ratio [IRR]= 9.47 [95% CI = 2.62- 34.30]). The mean increment of active lesions was 0.14 in G0 and 0.61 in G1, indicating that patients using fixed appliance had an approximately 4-fold greater risk of developing an additional active lesion than patients in the control group (adjusted IRR = 4.13 [1.94-8.79]). This study observed a significant association between the duration of fixed orthodontic treatment and the prevalence of gingival enlargement and active dental caries, as well as between the use of the fixed apparatus and the incidence and increase of active caries lesions after one year of monitoring.